Pengolahan Petai Cina sebagai Makanan Bernilai Ekonomi (Upaya Peningkatan Petani Petai Cina) - Mohammad Djaelani; Nurul Masithoh; Samuji Samuji (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Not many people know the benefits or uses of the lamtoro tree or what is commonly called petai cina which has the Latin name Leucaena Leucocephala which is a type of shrub. Through an empowerment program carried out in Wedungsari Village, Waru District, Sidoarjo Regency, where there are many petai cina farmers, a community service program was held with an orientation to support the productivity of farmers in the village and provide nutrition through food that has economic value. Through the community service method with stages of socialization, empowerment (training), independent appeals to evaluation, the results obtained were that this program showed the success of increasing farmer productivity by making various foods from petai cina that can be traded and become food that meets family nutrition at an economical price.